Relationship between dimensions of motivation towards employee performance / Muhamad Safiuddin Mohd Zulkifli and Muhamad Azwan Amirudin Aziz - Mohd Zulkifli, Muhamad Safiuddin; Aziz, Muhamad Azwan Amirudin (Faculty of Business and Management, 2016)
The employee performance is a continuous problem or issues that always be a major issue of the employee in company. This is not easy to motivate employee to give a high level of performance while do their work in an organization. This research has been conducted to investigate the dimension of motivation of employee which are rewards, job enrichment, training and team building. It is important to employee to give a high level of performance in work to help the organization achieve an objective goal’s successfully. The data collected through questionnaires among 113 respondents. The questionnaires were distributed to test the hypotheses proposed. The questionnaires designed based on four variables that are expected to be factors that motivate employee to better performance in work which are rewards, job enrichment, training and team building. From the results of the findings, it can be concluded that team building is most influence factor to employee performance.